The role of stability in the dynamics of learning, memorizing, and forgetting new coordination patterns - Tallet, J.; Kostrubiec, V.; Zanone, P. G. (Journal of Motor Behavior, 2008)
According to a dynamic theory of learning, how a new memory is formed depends on the stability of the nearest preexisting memories. To predict retention after practice, the authors analyzed how 15 participants memorized 2 bimanual coordination patterns (45° or 135° relative phase). The authors assessed (a) how participants memorized the required patterns with learning and (b) how the associated memory layout evolved. Results showed that a practiced 45° pattern near a very stable memory (0°) persisted, whereas a 135° pattern near a less stable memory (180°) was forgotten. Those findings corroborate the proposition that retention of coordination patterns depends on the stability of the extant motor memories. The authors discuss that proposal in terms of the coevolution of accuracy and stability with learning to predict persistence of required or false memories.